Computer application for studies of potential renewable energy sources - Linares, Juan Alejandro Martinez; Gámez, María Rodríguez; Pérez, Antonio Vázquez (International research journal of management, IT and social sciences, 2019)
Computer science's technologies have come to revolutionize the current era, the distributed generation and the introduction of new alternatives in the conception of the energy production, it is a factor that seen from the energy planning it allows to introduce the renewable energy sources (RES) as an element in the development of energetically sustainable territories. The space distribution of the natural resources that the RES generates, it has made necessary to develop advanced systems for the studies at space level. For the Needs of printing an analysis space and territorial of the RES studies, a geographical information system of renewable energy sources of was designed (SIGFRE), using free software, that offers information of the renewable potentials in the territory. This system is a tool that allows an appropriate way to offers information on the place (longitude and latitude) and the potentials (solar, hydric, wind, and biomass) that are generated in them.